Karakter Spasial dan Pengembangan Usaha Sarang Burung Walet di Jakarta Utara - Azis, Muh. Ikhsan; Siregar, Hermanto; Barus, Baba (P4W IPB, 2023)
Business unit of swallow's birdnest has great potential for economic activity because almost95% of Indonesian swallow's nest is exported. One of the efforts to develop a business is to carryout spatial analysis and production functions. This is necessary to determine the feasibility of aparticular system location and variables that affect a business. This study aims to determine thespatial character of the distribution of business units and several variables that influence theproduction process to develop this business. Analysis of spatial pattern of swallow's nest businessis done by using Average Nearest Neighbor (ANN). Income Analysis is done by calculating thedifference between receipts and costs. Production function analysis is done by using NormalityTest, Multicollinearity Test, Autocorrelation Test, and Heteroscedastic Test. The results showedthat the distribution of swallow's nest business units in North Jakarta was clustered, which wasonly found in 3 sub-districts i.e. Penjaringan, Tanjung Priok and Cilincing. The pattern showedthat the swallow’s nest business unit is profitable for business actors, it can attract the interest ofthe community and make competition more competitive. Production function are influenced by rawmaterials, water filter equipment, and electricity costs. Efforts to develop by reviewing thelicencing of the Swallow’s Birdnest Business units in North Jakarta, thus it remains in accordancewith the city spatial design plan and government policies.